Foetal Alcohol Syndrome Disorders-what do educators know? - Bradshaw, Dawn (2011)
Since the early 1970s the term Foetal Alcohol Syndrome Disorder has been used to describe characteristics associated with pre-natal exposure to alcohol in utero. This disorder is not confined to particular socio-economic groups, or specific countries, but is prevalent in many countries across the world to a greater or lesser extent. Much research has, so far, focused on the medical imperatives alongside the economic cost of the detection and treatment of children and adults with FASD. There has been less research in this country until the past year about how the condition manifests itself in the classroom. Through the use of a questionnaire, this paper attempts to address the question of what is known in the educational community about the effects of this debilitating disorder on the educational opportunities of those youngsters with a diagnosis, and what more needs to be known to effectively detect, support and facilitate the development of children with FASD in our classrooms and our communities.